The impact of peer assisted learning on mentors’ academic life and communication skill in medical faculty: A systematic review - Sabrina Intan Zoraya; Mutiara Tri Florettira; Rizma Adlia Syakurah; Abdillah Adipatria B. Azhar; Andika Okparasta; Tri Hari Irfani (International Journal of Public Health Science (IJPHS), 2021)
Peer assisted learning (PAL) was initiated to support the first-year students. In medical faculty, first-year students often find starting new academic life challenging. The impact from the peer mentors’ aspect is not widely explore. The aim of this study was to review studies that reported the impact of PAL programs on peer mentors in medical faculty, particularly on their academic life and communication skill. The DOAJ, PubMed Central, SciELO, and Science Direct databases advanced search used to conduct a systematic literature searching. Systematic search was performed according to preferred reporting items for systematic reviews and meta-analysis (PRISMA) checklist recommendations. Five studies were included. All of the reviewed studies shown the impact of PAL programs on mentors’ academic life. Three studies have shown both the impact of PAL programs on mentors on their academic life and communication skill. Studies in this review have shown positive impacts on mentors’ academic life and communication skill. Good communication skills, empathy, leadership and teaching skills will promote individual abilities and skills as a doctor, be it as a practitioner, or as an educator.